2012
DOI: 10.1038/jid.2011.274
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone-Inducible IL-6 Inhibits Elongation of Human Hair Shafts by Suppressing Matrix Cell Proliferation and Promotes Regression of Hair Follicles in Mice

Abstract: Autocrine and paracrine factors are produced by balding dermal papilla (DP) cells following dihydrotestosterone (DHT)-driven alterations and are believed to be key factors involved in male pattern baldness. Herein we report that the IL-6 is upregulated in balding DP cells compared with non-balding DP cells. IL-6 was upregulated 3  hours after 10-100  nM DHT treatment, and ELISA showed that IL-6 was secreted from balding DP cells in response to DHT. IL-6 receptor (IL-6R) and glycoprotein 130 (gp130) were expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
92
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 30 publications
3
92
0
3
Order By: Relevance
“…Cells were washed with phosphate-buffered saline and counterstained with hematoxylin for 10 minutes. HF specimens were immunostained as described before (Kwack et al, 2012) with isotype-matched normal rabbit IgG (R&D Systems) and Sox9 antibody as a negative control and a positive control, respectively.…”
Section: Immunostaining Of Sox9mentioning
confidence: 99%
“…Cells were washed with phosphate-buffered saline and counterstained with hematoxylin for 10 minutes. HF specimens were immunostained as described before (Kwack et al, 2012) with isotype-matched normal rabbit IgG (R&D Systems) and Sox9 antibody as a negative control and a positive control, respectively.…”
Section: Immunostaining Of Sox9mentioning
confidence: 99%
“…It was shown that DHT induces IL6 expression in the balding DP of human cells compared with nonbalding DP cells. This results in anagen-to-catagen transition in hair follicle and hair growth arrest [51]. Direction of the IL6 expression change by androgens is cell-specific.…”
Section: Dermal Papilla-specific Signaling Pathwaysmentioning
confidence: 99%
“…SPP1 (osteopontin) is expressed only during catagen but not in anagen or telogen in cultured rat vibrissae dermal papilla cells [115]. IL6 (interleukin 6) gene is a thoughtful candidate for DHT inducible catagen phase and regression of human hair shafts [51]. BMP2 is also a direct target of MIR106A [116].…”
Section: Hair and Scalp Disorders 154mentioning
confidence: 99%
“…method of paracrine signalling, it was shown that IL-6 acted on hair follicle keratinocytes to inhibit matrix cell proliferation and growth of the hair shaft, and consequently induced catagen (Kwack et al, 2012a). IL-6 has been previously demonstrated in vitro to mediate its effects via STAT5A in the JAK-STAT pathway, again implicating STAT5 in a further hair follicle signalling pathway in keratinocytes (Fujitani et al, 1997).…”
Section: Implications Of Stat5-mediated Signalling In the Hair Folliclementioning
confidence: 99%
“…STAT5 has appeared as part of signalling mechanisms within several investigations related to hair follicle cycling and as unpredicted side effects of other investigations; however, these investigations have not defined whether STAT5 could play an important role in the DP and the mesenchymal-epidermal interactions in these cells (Craven et al, 2006;Kwack et al, 2012a;Udy et al, 1997). Nevertheless, STAT5 appears at appreciable levels in microarray analyses in various investigations, and genetic knockout studies of STAT5 have shown to elicit a hair phenotype although its specific role in the DP compared to other skin components is unclear (Biernaskie et al, 2009;Driskell et al, 2009;Rendl et al, 2005;Udy et al, 1997).…”
Section: Summary and Significancementioning
confidence: 99%